Successful School Literacy Movement through Angkringan Baca - Prodyanatasari, Arshy; Marsida, Refki; Maharani, Anita; Kharisma, Dahniar Widya; Primanda, Lea Tarissha (Room of Civil Society Development, 2024)
This study emphasizes the importance of cultivating reading habits from an early age to support the success of the School Literacy Movement (Gerakan Literasi Sekolah or GLS) through the Angkringan Baca Program. The program revitalizes the school library to create a more inviting space that encourages student engagement with books. Conducted as part of the Collaborative Action Plan (RAK) of Teaching Campus 7, this community service project employed the Participatory Action Research (PAR) method. The project, implemented from February to June 2024 at SDN Bujel 3 in Kediri, targeted students from grades I to VI. The intervention was carried out in four stages, each designed to progressively increase student involvement. The results demonstrated a consistent rise in library visits each month, correlating with heightened interest in reading. This increased interest significantly enhanced students’ literacy skills, contributing to the broader goals of GLS by fostering critical thinking and academic success.